Vida y muerte de Jesús como referente para realizar una propuesta artística con estilo barroco. - Arteaga Galdeman, Agusto Eduardo (2021)
The present research work entitled: Life and death of Jesus as a reference to make an artistic proposal with a baroque style, it proposes to make use of pictorial language to create a series of 4 works concerning different verses of the life and death of Jesus, reviewing each relevant aspect for the investigation and of which the biblical text, the fundamental aesthetic categories are used as theoretical support of the style and pictorial references of Baroque artists to visualize important aspects of the image of Jesus that serves as the protagonist in the proposal. Making use of the inductive and deductive method, we arrive at judgments and reasoning processes from the accumulation of information collected, including the biographical and historical method, providing a more concrete and delimited approach; jointly, models, photographs, sketches and other traditional and technological resources are used. Finally, as a result, a work is reached in which the image of Jesus has been explored in a theoretical and technical way, which has lent itself to a personal interpretation far from any stimulus of criticism or propaganda.